Blended Learning and Critical Thinking in Acrylic Removable Partial Denture Theory Course - Fitriyanti, Fitriyanti; Marsigid, Didik; Wiyanti, Sri Wiwik (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This study aimed to examine the influence of blended learning model and critical thinking on students’ learning outcomes in acrylic removable partial denture theory course. The research was preceded by designing a blended lesson on acrylic removable partial denture theory course using the ASSURE learning model by considering objective conditions in the Department of Dental Engineering, Health Polytechnic, Ministry of Health, Jakarta II. Experiment was used as the research method with 2x2 treatment by level design. The data analysis was carried out using two- way analysis of covariance (ANCOVA). The results of the research found that students’ learning outcomes in the blended learning acrylic removable partial denture theory course were generally better than face-to-face learning, especially in the group of students with high critical thinking. The group of students with low critical thinking did not produce significantly different results.